2008
DOI: 10.1016/j.visres.2007.11.025
|View full text |Cite
|
Sign up to set email alerts
|

The roles of visual expertise and visual input in the face inversion effect: Behavioral and neurocomputational evidence

Abstract: Research has shown that inverting faces significantly disrupts the processing of configural information, leading to a face inversion effect. We recently used a contextual priming technique to show that the presence or absence of the face inversion effect can be determined via the top-down activation of face versus non-face processing systems [Ge, L., Wang, Z., McCleery, J., & Lee, K. (2006). Activation of face expertise and the inversion effect. Psychological Science, 17(1), 12-16]. In the current study, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
2
19
1
Order By: Relevance
“…Thus, it is possible that an unspecific mechanism that responds to first-order face configurations and resembling stimuli [37,52] quickly determines whether a visual stimulus is a face and thus will be preferentially attended to in primates. Computational models that have been applied successfully to investigate face processing [26,[140][141][142] may help solve the question whether such a mechanism is necessary to (re-)produce the characteristics of face processing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that an unspecific mechanism that responds to first-order face configurations and resembling stimuli [37,52] quickly determines whether a visual stimulus is a face and thus will be preferentially attended to in primates. Computational models that have been applied successfully to investigate face processing [26,[140][141][142] may help solve the question whether such a mechanism is necessary to (re-)produce the characteristics of face processing.…”
Section: Discussionmentioning
confidence: 99%
“…! used, the nonsense characters are farther apart in representational space, and hence better discriminated, as in the behavioral data (McCleery, et al, 2008).…”
Section: Additional Behavioral Data Accounted Formentioning
confidence: 99%
“…The basic idea of the model was that other race faces contain more information in the Shannon sense, and hence are more salient (see also (Zhang, et al, 2007) for a similar account). Finally, the model has been used to account for priming effects in the discrimination of nonsense characters (McCleery, et al, 2008). It had been shown that Chinese subjects primed to think of nonsense characters as a face discriminated them better than when they were primed to think of them as a Chinese character, when they differed configurally.…”
Section: Additional Behavioral Data Accounted Formentioning
confidence: 99%
“…It has been suggested that Chinese character recognition shares some similarities with face recognition (McCleery et al, 2008). They consist of strokes packed into a relatively constant square-shaped configuration, in contrast to words in most alphabetic languages, which are linear combinations of letters.…”
Section: Introductionmentioning
confidence: 99%